2020
DOI: 10.1101/2020.06.22.165969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online Transcranial Random Noise stimulation improves perception at high levels of visual white noise

Abstract: Keywords: tRNS1, perception2, stimulation3, noise4, psychophysics5, vision6. (Min.5-Max. 8) 26 27 tRNS improves vision-in-noise 2 Abstract (250 words) 28 29Transcranial random noise stimulation (tRNS), a relatively recent addition to the field of non-30 invasive, electrical brain stimulation, has been shown to improve perceptual and cognitive functions 31 across a wide variety of tasks. However, the underlying mechanisms of visual improvements caused 32 by tRNS remain unclear. To study this question, we employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 58 publications
1
8
1
Order By: Relevance
“…This explanation is consistent with findings from van der Groen and Wenderoth [15], who found no effects of performance at 1.5mA. Interestingly, however, Melnick et al [16] did find that 2mA hf-tRNS improved performance under high external noise levels compared to sham. This finding is consistent with an increased ability to filter external noise.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…This explanation is consistent with findings from van der Groen and Wenderoth [15], who found no effects of performance at 1.5mA. Interestingly, however, Melnick et al [16] did find that 2mA hf-tRNS improved performance under high external noise levels compared to sham. This finding is consistent with an increased ability to filter external noise.…”
Section: Introductionsupporting
confidence: 87%
“…Specifically, Melnick [16] presented a persistent current over a 20-minute period during task completion. However, we presented 20 minutes stimulation intermittently, using 2-minute stimulation periods with 1-minute breaks where stimulation ceased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For visual tasks ( N = 10), hf-tRNS acutely increases sensitivity for low contrast visual stimuli as demonstrated for contrast detection task ( van der Groen and Wenderoth, 2016 ), orientation discrimination task ( Melnick et al, 2020 ), lateral visual masking protocols ( Battaglini et al, 2019 ), and exploring stimulation effects using visual stimuli with various properties ( Battaglini et al, 2020 ). It was further shown that delivering central noise via hf-tRNS influences state-switching dynamics of binocular rivalry ( van der Groen et al, 2019 ) and accelerates perceptual decision-making in a motion discrimination task ( Campana et al, 2016 ; Ghin et al, 2018 ; van der Groen et al, 2018 ; Pavan et al, 2019 ; O’Hare et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%